Citizens, experts, and the environment : the politics of local knowledge - Fischer, Frank, 1942- (E-Duke books scholarly collection., 2000)
Claims that the problematic communication gap between experts and ordinary citizens is best remedied by a renewal of local citizen participation in deliberative structures.